The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/comjnl/bxab214
|View full text |Cite
|
Sign up to set email alerts
|

An Educational Data Mining System For Predicting And Enhancing Tertiary Students’ Programming Skill

Abstract: Educational Data Mining (EDM) has become a promising research field for improving the quality of students and the education system. Although EDM dates back to several years, there is still lack of works for measuring and enhancing the computer programming skills of tertiary students. As such, we, in this paper, propose an EDM system for evaluating and improving tertiary students’ programming skills. The proposed EDM system comprises two key modules for (i) classification process and (ii) learning process,. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The structural model of English classroom teaching is a stable structural form of the process of classroom teaching activities, including the process structural style composed of elements, links, and steps of classroom teaching activities. The application of big data, learning analysis and other technologies has made important changes in the structure of English classroom teaching (Marjan et al, 2023). Traditional classroom teaching is centered on teachers and teaching materials; material is taught by teachers and accepted by students.…”
Section: Construction Of Intelligent Classroom Learning Modelmentioning
confidence: 99%
“…The structural model of English classroom teaching is a stable structural form of the process of classroom teaching activities, including the process structural style composed of elements, links, and steps of classroom teaching activities. The application of big data, learning analysis and other technologies has made important changes in the structure of English classroom teaching (Marjan et al, 2023). Traditional classroom teaching is centered on teachers and teaching materials; material is taught by teachers and accepted by students.…”
Section: Construction Of Intelligent Classroom Learning Modelmentioning
confidence: 99%
“…The results showed that this approach provides an effective way to provide and predict early grade assessments of underperforming students, thereby more effectively guiding the student. According to Marjan et al [19], an educational data mining (EDM) system was proposed to measure and develop higher education students’ computer programming skills. The proposed EDM system includes two key modules for (i) the classification process and (ii) the learning process.…”
Section: Introductionmentioning
confidence: 99%